2012
DOI: 10.4317/medoral.17583
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum ctx in 50 oral surgical patients treated with oral bisphosphonates

Abstract: Objectives: To determine whether there is a relationship between the total BP dose administered and the variations in serum CTX concentration. Study design: The study included 50 patients requiring dental implant surgery and treated with oral BPs, seen in an Oral Surgery and Implantology Unit between January 2007 and June 2009. The patients were divided into two groups: those in which the medication was not suspended before obtaining the laboratory test sample, and those patients referred from other dental cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…12,13,[22][23][24] Thus, eight studies were analyzed and form the basis of this review. [14][15][16][25][26][27][28][29] All eight of the selected studies were prospective clinical trials. They included a total of 1442 patients with a mean age of 66.7 years.…”
Section: Resultsmentioning
confidence: 99%
“…12,13,[22][23][24] Thus, eight studies were analyzed and form the basis of this review. [14][15][16][25][26][27][28][29] All eight of the selected studies were prospective clinical trials. They included a total of 1442 patients with a mean age of 66.7 years.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a clinical study by Lazarovici et al evaluating both osteoporosis and cancer patients found a CTX value of <150 pg/mL was significantly associated with BRONJ development (odds ratio=5.27, p=0.004). 10 In contrast to these findings, Bagan et al found no relationship between serum CTX and the risk of developing BRONJ in patients receiving both oral 20 and intravenous BP’s. 21 Kunchur et al evaluated patients on oral BP (n=215) and intravenous BP (n=7) scheduled for tooth extractions and reported that CTX test did not predict the development of BRONJ; however, a value of less than 150 to 200 pg/mL suggested patients in the “risk zone”.…”
Section: Discussionmentioning
confidence: 91%
“…According to Baim and Miller, serum CTX as a predictor of BRONJ has yet to receive rigorous evidence‐based validation, and there are currently insufficient data to support using CTX levels to guide the modification of bisphosphonate therapy in such a way as to minimise the risk of developing BRONJ. Flichy‐Fernández et al . evaluated 50 patients under oral bisphosphonate therapy and concluded that it is doubtful whether the serum CTX test is of help in determining osteonecrosis risk in patients treated with these medications.…”
Section: Management Of Patients Under Alendronate Therapymentioning
confidence: 99%
“…Some authors agree 4,56-60 and others disagree [61][62][63][64][65][66] with these concepts of drug holiday and CTX defended by Marx et al 6 According to Baim and Miller 63 , serum CTX as a predictor of BRONJ has yet to receive rigorous evidence-based validation, and there are currently insufficient data to support using CTX levels to guide the modification of bisphosphonate therapy in such a way as to minimise the risk of developing BRONJ. Flichy-Fern andez et al 67 evaluated 50 patients under oral bisphosphonate therapy and concluded that it is doubtful whether the serum CTX test is of help in determining osteonecrosis risk in patients treated with these medications. Bag an et al 61 evaluated the serum CTX levels of 15 BRONJ patients treated with zoledronic acid and found a mean of 294.10 AE 76.27 pg/ml, which disagrees with the findings of Marx et al 6 Lee et al 68 consider BRONJ a rare complication and are of the opinion that oral surgery procedures in this group of patients can be safely performed without the need to include the CTX test in the preoperative management of the oral bisphosphonate patient 68 .…”
Section: Oral Surgery Serum C-terminal Telopeptide Test (Serum Ctx) mentioning
confidence: 99%